Improving Regional Fiscal Capacity in Central Java Province Indonesia - Shanty Oktavilia; Fafurida Fafurida; Yozi Aulia Rahman; Ririn Bella Silvia (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
This study discusses the development of fiscal capacity in Central Java, Indonesia. The purpose of this study is to analyze internal and external factors that increase regional fiscal capacity, and formulate strategies by analyzing internal and external elements to obtain four alternative strategies namely 'strength - opportunity' strategy, 'strength - threat' strategy, 'weakness - opportunity' strategy and Strategy for 'weaknesses - threats'. This study uses secondary data to analyze indicators of regional fiscal capacity and primary data collected through focused discussions, to analyze strategies. The results of the analysis indicate that there are several main strategies to increase regional fiscal in Central Java Province, namely the program of intensification and extensification of regional taxes; improving the quality of human resources with special competencies in the field of taxation; synergy and internal coordination between regional government institutions; improvement of the supervision system for taxpayers; realizing clear and legal regional regulations, simplifying the mechanism for managing investment licenses in Central Java and optimizing regional revenues through modernizing the collection of taxes and levies by utilizing technology. Modernization of increasing regional fiscal capacity will encourage the achievement of equitable regional revenue, increase public participation, administrative efficiency, consistent law enforcement, and improve the level of public confidence in the implementation of good governance.